PENGEMBANGAN BAHAN AJAR TEKS PROSEDUR BERTEMA MAKANAN TRADISIONAL UNTUK SISWA SMP/MTs KELAS VII - Rismanto, Arif; Mulyaningtyas, Rahmawati (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2023)
Indonesian teaching materials for procedural text material with the theme of traditional food are still rarely found. Teaching materials that are currently developing do not consider graphical aspects such as choosing colors, typefaces, and using pictures or illustrations. Therefore, it is necessary to develop teaching materials for traditional food-themed procedure text materials that have attractive designs with contemporary graphics, communicative language, simple material, and consistent presentation of themes. This research aims to produce teaching materials for traditional food-themed procedure texts with content, presentation, language, and graphics that are feasible to be implemented in learning. This research uses the development model of Borg and Gall version of Sukmadinata which includes (1) preliminary study; (2) design and development; and (3) testing of teaching materials. The types of data obtained from this teaching material development research are qualitative data and quantitative data. The results of the final testing of teaching materials by experts reached a percentage of 99%. Thus, the teaching materials for traditional food-themed procedure texts that have been developed have very feasible qualifications and can be implemented in Indonesian language learning.